PENGARUH PROMOSI DAN KUALITAS PRODUK KCA (KREDIT CEPAT AMAN) TERHADAP KEPUTUSAN NASABAH PADA PT PEGADAIAN (PERSERO) UNIT PANARUKAN DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING - Rahayuk, Sri; Prasetyo, Indra; Sugiarno, Yuventius (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
From time to time, public demand for credit increases. The PT Pegadaian (PERSERO) financial report stated that turnover and outstanding loans for each type of credit experienced growth from the previous year, thereby increasing capital rental income. This provides an opportunity for PT Pegadaian as an alternative to provide credit services to low-income groups of people who lack credit facilities from bank financial institutions. PT Pegadaian (Persero) provides credit very easily and quickly. One of the credit services provided to the public at pawnshops is a product called KCA. KCA is a superior product that is respected by the public. In general, the aim of this research is to describe, prove and analyze the influence of promotions and KCA product quality on customer decisions through customer satisfaction at PT Pegadaian (Persero) Panarukan Unit. The variables used are promotion, KCA product quality, satisfaction and customer decisions. The type of research is quantitative research. The research sample was collected using a purposive sampling method of 105 customers who had chosen more than one KCA product. The analysis tool used is path analysis. After conducting path analysis, it was found that promotion and product quality had a significant direct and indirect effect on customer decisions through satisfaction.